STRUCTURE AND CATION DISTRIBUTION OF Cd-Zr CO-SUBSTITUTED NICKEL SPINEL FERRITE - PATIL, B.U. (Innovare Journal of Sciences, 2020)
Cd-Zr co-substituted nickel spinel ferrite was prepared using standard ceramic method of preparation.The prepared samples were characterized by XRD for its structural analysis. The lattice parameter, particle size and X-ray density were obtained from the XRD data. Further, using XRD data the cation distribution was obtained revealing that the Zr4+ ions occupy both tetrahedral and octahedral sites.